Mucosa-associated lymphoid tissue lymphoma translocation protein 1 exaggerates multiple organ injury, inflammation, and immune cell imbalance by activating the NF-κB pathway in sepsis - Wang, Yane; Liu, Zhimin; Zhang, Mengli; Yu, Bo; Ai, Fen (Frontiers in Microbiology, 2023)
Objective: Mucosa‐associated lymphoid tissue lymphoma translocation protein 1 (MALT1) modulates the inflammatory immune response and organ dysfunction, which are closely implicated in sepsis pathogenesis and progression. This study aimed to explore the role of MALT1 in sepsis-induced organ injury, immune cell dysregulation, and inflammatory storms. Methods: Septic mice were constructed by intraperitoneal injection of lipopolysaccharide, followed by overexpression or knockdown of MALT1 by tail vein injection of the corresponding lentivirus. Mouse naïve CD4+ T cells and bone marrow-derived macrophages were treated with MALT1 overexpression/knockdown lentivirus plus lipopolysaccharide. Results: In the lungs, livers, and kidneys of septic mice, MALT1 overexpression exaggerated their injuries, as shown by hematoxylin and eosin staining (all P<0.05), elevated cell apoptosis, as reflected by the TUNEL assay and cleaved caspase-3 expression (P<0.05 in the lungs and kidneys), and promoted macrophage infiltration, as illustrated by CD68 immunofluorescence (P<0.05 in the lungs and kidneys). Meanwhile, in the blood, MALT1 overexpression reduced T-helper (Th)1/Th2 cells, increased Th17/regulatory T-cell ratios (both P<0.05), promoted systematic inflammation, as revealed by tumor necrosis factor-α, interleukin-6, interleukin-1β, and C-reactive protein (all P<0.05), elevated oxidative stress, as shown by nitric oxide (P<0.05), superoxide dismutase, and malondialdehyde (P<0.05), and enhanced liver and kidney dysfunction, as revealed by an automatic animal biochemistry analyzer (all P<0.05 except for aspartate aminotransferase). However, MALT1 knockdown exerted the opposite effect as MALT1 overexpression. Ex vivo experiments revealed that MALT1 overexpression promoted the polarization of M1 macrophages and naïve CD4+ T cells toward Th2 and Th17 cells (all P<0.05), while MALT1 knockdown attenuated these effects (all P<0.05). Mechanistically, MALT1 positively regulated the nuclear factor-κB (NF-κB) pathway both in vivo and ex vivo (P<0.05). Conclusion: MALT1 amplifies multiple organ injury, inflammation, oxidative stress, and imbalance of macrophages and CD4+ T cells by activating the NF-κB pathway in sepsis.